Metal−Organic Frameworks for Environmental Remediation - Ghosh, Pooja, editor 645609; Kumar, Smita S., editor 645610; Singh, Lakhveer, editor 645611; ACS Publications (Online service) 645714 (Washington, DC : American Chemical Society, 2021)
"Addressing Pollution Issues with MOFs. Metal-organic frameworks (MOFs) have emerged as highly customizable catalysts based on their unique features. Recent studies have developed specific MOFs for many applications. As part of a three-volume set (1393-1395), this volume provides an overview on MOFs used in environmental remediation, including synthesis, characterization, and examples of applications. Materials scientists, chemical engineers, and environmental scientists will find this work useful, as will students learning about this active area of research."-- Provided by publisher.